A screening strategy identified LsNHL10 as an important regulator of grafting-enhanced cold tolerance in bottle gourd - Haiyan Wang; Xiaohua Wu; Xiao Guo; Jian Wang; Min Wang; Xinyi Wu; Baogen Wang; Guojing Li; Pei Xu; Ying Wang (Plant Stress)
Cold stress is one of the predominant abiotic constraints in the cultivation practices of vegetable crop. Bottle gourd [Lagenaria siceraria (Mol.) Standl.], a thermophilic Cucurbitaceae vegetable crop, exhibits significant sensitivity to cold stress. However, current researches remain relatively limited in elucidating the molecular mechanisms and physiological responses to cold stress in bottle gourd. Here, we analyzed the morphological and physiological indicators of heterografted bottle gourd-pumpkin seedlings (Ls/Cm) and allografted bottle gourd-bottle gourd seedlings (Ls/Ls) under cold stress (1 °C) at different time points (0, 3, 6, 9, 12 h). It was found that heterologous grafting significantly enhanced the cold stress tolerance of bottle gourd by more resistant phenotypes, higher maximal photochemical efficiency (Fv /Fm), lower malondialdehyde (MDA) content and relative electric conductivity (REC), greater increase in superoxide dismutase (SOD), peroxidase (POD) activity, and proline (PRO) content. Further, we developed a screening strategy for identifying cold stress-responsive genes in grafted bottle gourd seedings, and by applying this screening strategy, an important cold-stress candidate gene LsNHL10 was identified. Tissue-specific profiling using RT-qPCR revealed that LsNHL10 was abundantly expressed in young leaves and subcellular localization confirmed it was localized to cell nucleus, cytoplasm and chloroplast. The functional analysis demonstrated that transient overexpression of LsNHL10 enhanced the cold stress tolerance of bottle gourd, whereas transient silencing weakened that. Our study provided a screening strategy for cold stress-responsive gene identification in grafted bottle gourd and revealed the mechanistic basis that conferred adaptive benefits of bottle gourd plants under cold stress.